Hubungan antara Secure Attachment dengan Kompetensi Sosial pada Remaja di SMAN 5 Sarolangun - HidayahHidayah, Putri Annur; Irdam, Irdam; Mariana, Rina (TSAQOFAH, 2026)
Social competence is an important aspect of adolescent development because it relates to the ability to establish relationships, adapt, and interact positively in the school environment. This study aims to determine the relationship between secure attachment and social competence among students of SMAN 5 Sarolangun. This study employed a quantitative approach with a correlational design. The research sample consisted of 122 students selected through the random sampling technique. Data were collected using a secure attachment scale and a social competence scale. The research instruments had undergone validity and reliability testing, with the validity coefficients of the secure attachment scale ranging from 0.341 to 0.628 and a reliability coefficient of 0.885, while the validity coefficients of the social competence scale ranged from 0.310 to 0.735 with a reliability coefficient of 0.907. The results show a very significant positive relationship between secure attachment and social competence (r = 0.582; p = 0.000; p < 0.01). These findings indicate that the higher the secure attachment possessed by students, the higher their social competence. In addition, secure attachment provides an effective contribution of 33.9% to social competence. The conclusion of this study emphasizes that secure attachment plays an important role in supporting adolescents’ social competence in the school environment. The implications of this study emphasize the importance of secure relational support between adolescents and significant figures to strengthen students’ social development.